Comparing Different Typologies of Physical Activities With a Focus on Motivation - Hsu, Rafael Ming Chi Santos; Cardoso, Fernando Luiz; Varella, Marco Antonio Corrêa; Pires, Edvane Marlene; Valentova, Jaroslava Varella (Frontiers in Psychology, 2022)
Different classifications of physical activities (PA) exist, however they lack precise grouping criteria and tend to vary according to each author. Among other factors, individual level of motivation is considered an important aspect for to PA maintenance. In this research, we aimed to (1) compare several PAs according to intrinsic (Interest/Enjoyment and Competence) and extrinsic (Appearance, Fitness/Health and Social) motives, and (2) to analyse PAs with and without previous grouping, to explore which PAs would be more similar according to the different motivational subscales. We recruited 1,421 physically active Brazilian participants (mean age = 26.83, SD = 10.49), who stated themselves as physically active. Among the main results, we found that some PAs were consistently separated themselves from others on regarding motivational subscales. For example, such as participants practicing Walking showed less Interest/Enjoyment and Competence than several other PAs. Pilates was marked highlighted by a particularly low Social motivation compared to other PAs. Further, using different categorization of PAs suggested by previous authors also showed consistent distinctions considering each motivational subscale. Specifically, one group of PA scored higher than the others on intrinsic motivation (e.g., PA more Complex, Team, Vigorous, Hybrid, and Combative), and the reverse was found when considering Appearance and Fitness/Health motives (e.g., PA more Organized, Individual, Moderate, Strength, and Rhythmic). Our results thus provide initial evidence toward possible new methods of grouping PA types that can improve maintenance behavior, using motivation as a grouping factor.